Digitalization and the future of Management Learning: New technology as an enabler of historical, practice-oriented, and critical perspectives in management research and learning. Issue 1 (February 2020) - Laurell, Christofer; Sandström, Christian; Eriksson, Klas; Nykvist, Rasmus
How are historical, practice-oriented, and critical research perspectives in management affected by digitalization? In this article, we describe and discuss how two digital research approaches can be applied and how they may influence the future directions of management scholarship and education: Social Media Analytics and digital archives. Our empirical illustrations suggest that digitalization generates productivity improvements for scholars, making it possible to undertake research that was previously too laborious. It also enables researchers to pay closer attention to detail while still being able to abstract and generalize. We therefore argue that digitalization contributes to a historical turn in management, that practice-oriented research can be conducted with less effort and improved quality and that micro-level data in the form of digital archives and online contents make it easier to adopt critical perspectives.